The Oxford handbook of Islam and women - Afsaruddin, Asma, 1958- (New York : Oxford University Press, 2023)
""Islam and Women" is a very broad topic and as complex as the lives of women that it encompasses in a broad swath of the world. In its wide-ranging coverage of issues subsumed under this umbrella topic, this volume is purposefully multi-disciplinary. The chapters are authoritative contributions from well-known scholars who are at the cutting-edge of scholarship on inter alia Qur'anic hermeneutics and hadith studies, women's legal and social rights, women's scholarly, cultural, economic, and political activities in the pre-modern and modern Islamic societies, the rise of Islamic feminism and women's activism and movements in a number of contemporary Muslim-majority countries and regions, including Egypt and North Africa, Turkey, Iran, Palestine, Lebanon and Syria, Saudi Arabia and the Gulf region, South and Southeast Asia, and in Muslim-minority contexts in western Europe, the United States, and China. The politicized portrayal of Muslim women, especially of those who wear the headscarf (hijab), in the global Western-dominated media and the weaponization of their bodies in certain kinds of political and feminist discourses also receive attention. These chapters delineate a broad spectrum of views on these key issues that are prevalent inside and outside of academia and provide sophisticated and careful analysis of textual sources and of broad sociological and political trends. Many of these essays emphasize above all the diversity present in Muslim women's lives, both in the pre-modern and modern periods, and pay close attention to the historical and political contexts that shaped their lives and framed the thinking and actions of key female figures throughout Islamic history. Such an approach results in fine-grained macro- and micro-studies of Muslim women's lives that problematize reified assumptions of gender and agency in the context of Muslim-majority societies"--
Includes bibliographical references and index.
ENH
Karim International
Keywords: Women in Islam; Muslim women; Islam